PENGARUH VARIASI KECEPATAN POTONG DAN GERAK MAKAN PADA PROSES PEMESINAN BUBUT TERHADAP DIMENSI DIAMETER MENGGUNAKAN CMM - Febrianto (Universitas Muhammadiyah Surabaya, 2025)
One of the most frequently used machine tools is lathe. Lathe parameters such as cutting speed and feeding motion determine the rate of material processing and the dimensions of the final result. The use of CMM provides advantages in dimensional measurement accuracy so that it can be used to evaluate the effect of cutting speed and feed motion on the lathe machining process. In this study, a product with an outside diameter of 62 mm and an inside diameter of 51.55 mm was used. The finishing process on the inner diameter becomes a diameter of 51.949 mm with a tolerance of ± 0.02. The amount of cutting speed used is 280 m/min, 340 m/min, and 440 m/min, as well as feeding motion of 0.1 mm/rev, 0.15 mm/rev, and 0.3 mm/rev. The results showed that variations in cutting speed and feeding motion can affect the diameter dimensions of the product. The measurement results tend to decrease from the standard with a value of 51.9467 mm to 51.9058 mm. The value of similarity from the largest with theory 99.9996% and actual 99.9978% to the smallest with theory 99.9986% and actual 99.9583%. The quality numbers range from IT 2 to IT 8 which means the use of modern machines (CNC) can be used well if the use of parameters is appropriate. The best combination to improve consistency and accuracy is 280 m/min cutting speed and 0.1 mm/rev feed motion. Keywords: lathe, CMM, diameter, accuracy, quality score